Analysis of Milk Powder by Direct Nebulization into Inductively-coupled Plasma - Lee, C. K.; Finlayson, R. K. (1986)
Sample preparation has always been a tedious but important step in analysis involving Inductively Coupled plasma emission spectrometry. In addition, it may also be a source of sample contamination. The present work attempts to overcome these problems by nebulizing milk powder suspensions directly into the plasma. Various infant and full cream milk powders were dispersed in water as well as 0.5% triton-X solution. The suspensions were then analysed for calcium, phosphorus, iron, magnesium and sodium. These elements were successfully determined using inorganic standards with the addition of an internal standard to correct for the difference in viscosities.